Determination of the Cavitation Pressure Threshold in Focused Ultrasound Wave Fields applied to Sonosensitive, Biocompatible Nanoparticles for Drug Delivery Applications - George, Benedikt; Lehner, Markus; Fink, Michael; Rupitsch, Stefan; Hiltl, Pia-Theresa; Savsek, Ula; Lee, Geoffrey; Ermert, Helmut (Current Directions in Biomedical Engineering 2020, 2020)

Formulation, process, and storage strategies for lyophilizates of lipophilic nanoparticulate systems established based on the two models paliperidone palmitate and solid lipid nanoparticles - Trenkenschuh, Eduard; Savsek, Ula; Friess, Wolfgang (International Journal of Pharmaceutics, 2021)
Lyophilization formulation and process development for lipophilic nanoparticle (NPs) products is highly challenging as the NPs have a low colloidal stability. We compared two different NP types, pure paliperidone palmitate nanocrystals and trimyristin solid lipid nanoparticles regarding formulation, process, and storage stability aspects. Freeze-thaw studies were conducted to investigate the basic formulation aspects such as buffer type, pH, and ionic strength as well as different cryoprotectants. In freeze-drying conventional ramp freezing was performed and compared to freezing with an annealing step added or with controlled ice nucleation. Different formulations were lyophilized and tested for short-term storage stability up to 6 weeks. Samples were analyzed for particle size, subvisible particle number, specific surface area, residual moisture, crystallinity, and glass transition temperature. Sucrose significantly better stabilized both NP types against freeze-thaw stress compared to mannitol demonstrating the importance of a fully amorphous matrix. While the impact of buffer type and pH was negligible, the aggregation propensity of NPs was reduced in presence of NaCl. The freezing step also impacted NP aggregation but the effect was less important than the formulation design. Surfactants did not necessarily improve the colloidal stability but resulted in a lower glass transition temperature of the lyophilizates and may cause phase separation which limits storage stability. This hurdle can be overcome by using a hydroxypropyl-beta-cyclodextrin/ sucrose mixture as cryoprotectant. In general, we could show a similar freeze-drying behavior of the two NP types. Thus, we established a formulation and process approach to achieve stable lyophilizates of lipophilic NPs based on two different types of NPs. The general rules should be transferable to other NPs facilitating lyophilization development.
CRIS-Team WoS Importer:2021-09-10

Investigation of Inertial Cavitation Induced by Modulated Focused Ultrasound Stimuli - George, Benedikt; Savsek, Ula; Fischer, Dagmar; Ermert, Helmut; Rupitsch, Stefan Johann (Current Directions in Biomedical Engineering, 2022)
A passive cavitation detection setup is used to assess and verify the capability of frequency- and amplitude-modulated ultrasound burst signals on the generation of inertial cavitation. The measurements were conducted with a flow-through tissue-mimicking phantom with a canal of dc = 1 mm in diameter simulating a fine blood vessel. By means of a flow velocity of vf = 50 mm/s circulating blood in the cardiovascular system is imitated. Applying signal frequencies from f = 550 − 950 kHz and peak rarefaction pressures in a range from pPRFP ≈ 0.17 − 1.81 MPa, various ultrasound stimuli with alternating signal parameters were investigated in the absence and presence of a talcum-water mixture acting as cavitation nuclei. By evaluating the broadband emissions in the frequency domain and calculating the voltage spectral density Srm, the results can be compared. The findings of the present study demonstrate that each ultrasound stimulus triggers a similar strength of cavitation noise at the same Mechanical Index, representing a certain pressure. Over the whole frequency and Mechanical Index (pressure) range, each ultrasound signal type generates a voltage spectral density from Srm = 0.25 − 2.25 V/√Hz.
CRIS-Team Scopus Importer:2022-09-30
Keywords: Focused ultrasound; Inertial cavitation; Modulated signals

Investigation of Inertial Cavitation of Sonosensitive and Biocompatible Nanoparticles in Flow - Through Tissue- Mimicking Phantoms Employing Focused Ultrasound - George, Benedikt; Savsek, Ula; Fischer, Dagmar; Ermert, Helmut; Rupitsch, Stefan J. (Current Directions in Biomedical Engineering, 2021)
A promising approach to drug delivery applications for chemotherapeutics is the use of drug carriers to reduce the total amount of cytostatics, minimizing side effects. In addition, the carriers, loaded with the drug, can be guided to the tumorous tissue via the vascular system, which enables a local drug release (LDR). In our case, LDR is activated due to the sonosensitive behavior of the nanocapsules by inertial cavitation (IC) caused by focused ultrasound (FUS). Thereby, IC is excited by employing sound pressures within the recommended limit allowed for diagnostic ultrasound. In order to verify this drug delivery approach for its clinical suitability, a tissue-mimicking flow -through phantom, containing a small vessel, is used. Investigations have shown that the drug releasing cavitation effect associated with the sonosensitive and biocompatible nanocapsules also occurs in fine vessel structures, even in the case of moving particles and vessel diameters dc smaller than the wavelength λ.
CRIS-Team Scopus Importer:2024-12-16
Keywords: flow - through.; Inertial cavitation; nanoparticles; tissue - mimicking phantom